The orphan regulator ReiD of Salmonella enterica is essential for myo‐inositol utilization. Issue 3 (6th October 2014) - Rothhardt, Johannes E.; Kröger, Carsten; Broadley, Steven P.; Fuchs, Thilo M.
Summary In Salmonella enterica serovar Typhimurium (S. Typhimurium), the genomic island GEI4417/4436 is responsible for the utilization of myo‐inositol (MI) as carbon and energy source. Here, we report the characterization of a novel, island‐encoded positive autoregulator termed ReiD (STM4423) that is specific to certain S. enterica strains and Escherichia coli strain ED1a able to use MI. ReiD was essential for growth with this polyol and also contributed to S. Typhimurium proliferation in swine caecum content. Providing higher copy numbers of ReiD reduced the long lag phase of 2 days during growth of S. Typhimurium in MI medium by 50%. In a heterologous host, expression of ReiD activated the transcription from the promoter of iolE/iolG, whose products catalyse the initial two steps in MI degradation. Episomal expression of iolE/iolG1 rescued the otherwise zero growth phenotype of a reiD deletion mutant in MI medium. Gel mobility shift assays with purified ReiD demonstrated directed interaction of ReiD with its own promoter and that of iolE. The repressor IolR bound the reiD promoter, implying that reiD is part of the IolR regulon. Taken together, the regulator ReiD is a trigger to accelerate the switch from more easily accessible nutrients to MI utilization by S. Typhimurium.